FAUNA DE COLEOPTERA SCARABAEOIDEA DE CUETZALAN DEL PROGRESO, PUEBLA , MÉX ICO - Carrillo Ruiz, Hortensia; Morón Ríos, Miguel Ángel (Instituto de Ecología, A.C., 2003)
In this work a comparative analysis of the scarab beetles of Cuetzalan del Progreso, Puebla, México is presented. Data were obtained from March 1998 to March 1999 in tropical rain forest, induced pasture land and secondary vegetation, between 400-1000 m above sea level. Records of 7 subfamilies, 18 subtribus, 34 genera and 63 species are presented. The greatest specific diversity corresponds to Dynastinae (21 spp), Melolonthinae (13 spp), Scarabaeidae (13 spp) and Passalinae (8 spp). The 50% of the species are concentrated in the genera: Phyllophaga (9 spp), Cyclocephala (9 spp), Onthophagus (5 spp), A taenius (3 spp), Passalus (3 spp) and A nomala (2 spp). We present a parsimony analysis of endemicity in order to know the relationships between the fauna of Cuetzalan and other Mexican localities. The fauna of Cuetzalan de Progreso is closely related to the fauna of the humid mountains of the northeast of Hidalgo. A key to the taxa found in Cuetzalan del Progreso is included.